Intrarater reliability of an adductor squeeze test with professional basketballers - Webster, D. K.; Jolley, D. J. (International Journal of Athletic Therapy & Training, 2023)
Groin injuries are common in basketball. Reduced adductor strength is a risk factor for injury, so monitoring strength can be important for injury prevention. This research assessed the reliability of an adductor strength test in male professional basketballers in preseason. Strength was tested using a sphygmomanometer between the knees at 0°, 45°, and 90° of hip flexion, in two trials. There was no difference in mean scores between trials. All conditions had moderate or higher intrarater reliability, with 45° hip flexion the most reliable. This test can be used to identify and monitor players with increased adductor injury risk.